How Do Candidates Perform When Repeating the American Board of Physical Medicine and Rehabilitation Certification Examinations?. (October 2016) - Robinson, Lawrence R.; Sabharwal, Sunil; Driscoll, Sherilyn; Raddatz, Mikaela; Chiodo, Anthony E.
ABSTRACT: Objective: The objective of this study was to examine the likelihood of passing the Part I and Part II American Board of Physical Medicine and Rehabilitation (ABPMR) certification examinations after initially failing. Design: This was a retrospective review of candidates who had taken the ABPMR initial certification examinations between 2010 and 2014. Results: Passing rates declined markedly with repeated attempts for both part I and part II. Passing rates (mean [95% confidence interval]) for part I were first attempt, 90% (87%–92%); second attempt, 58% (52%–66%); third attempt, 41% (26%–54%); fourth or greater attempt, 17% (3%–31%). For part II, the passing rates were first attempt, 87% (82%–92%); second attempt, 65% (56%–75%); third attempt, 41% (17%–65%); fourth or greater attempt, 20% (0%–59%). Those who were closer to the passing score on their initial attempt had a greater chance of passing on successive attempts. Conclusions: Passing rates for the ABPMR certification examination decline markedly with greater numbers of attempts. Those who fail again after one repeat attempt should rethink their examination preparation strategy before attempting the examination again.